Effect of genotype, storage and processing on the polyphenolic content, composition, in vitro anti-cancer activity and sensory attributes of colored-flesh potatoes - Madiwale, Gaurav, author; Vanamala, Jairam, advisor; Stone, Martha, advisor; Reddivari, Lavanya, committee member; Bunning, Marisa, committee member; Holm, David, committee member (Colorado State University. Libraries, 2012)
The potato (Solanum tuberosum L.) is the world's third largest food crop with per capita consumption of ~126 lbs. annually in the US. The 2010 US Potato Board Report revealed that over the past ten years, while consumption of traditional potatoes (mashed, baked, fried, steamed, boiled and french fries) declined, specialty/colored potato consumption increased by 17%, possibly due to their putative health benefits. Specialty/colored potatoes, which are rich in anti-proliferative and pro-apoptotic anthocyanins and/or carotenoids, can be an attractive "delivery system" for these bioactive compounds in humans. However, colored potatoes can undergo 3-6 months of storage before processing/consumption and the effect of storage and processing on their anti-cancer properties remains unknown. We hypothesized that potatoes retain polyphenolic content (TP), antioxidant activity (AA) and chemopreventive properties against early stage (HCT-116) and advanced stage (HT-29) human colon cancer cells even after 3 months of storage and processing (baking and chipping). To test this hypothesis, we utilized white-, yellow- and purple-fleshed potato clones and tested their phenolic (Folin-Ciocalteu) and anthocyanin (pH-differential) content, antioxidant activity (ABTS and DPPH), metabolite profile (UPLC-MS), anti-cancer properties (cell proliferation via cell counting and BrdU assays, and apoptosis via Caspase-Glo 3/7 assay), and sensory attributes (9-point hedonic scale). Purple-fleshed potatoes had higher phenolic content and antioxidant activity as compared to their white- and yellow-fleshed counterparts. The antioxidant activity of all clones increased with storage; however, an increase in total phenolic content was observed only in purple-fleshed clones. Baking caused minimal losses while chipping reduced the phenolic and anthocyanin content, and antioxidant activity of the potatoes. With storage, total phenolic and anthocyanin content, and antioxidant activity increased in baked samples while in the chipped samples, they remained constant. Principal component analysis of approximately 1600 peaks obtained by UPLC-MS analysis revealed that storage caused a shift in the metabolite profiles of potato clones. In general, ethanol extracts of uncooked, baked and chipped samples suppressed proliferation and elevated apoptosis (p < 0.05) in human colon cancer cell lines (HCT-116, HT-29). However, chipped samples did not have any effect on HT-29 cell lines. Anti-proliferative and pro-apoptotic properties of baked potatoes were similar to that of raw potatoes while chipping caused a significant reduction in the biological activity. Storage generally negatively affected the anti-cancer properties of the potato extracts. Sensory analysis revealed comparable acceptance of purple-fleshed baked and chipped potatoes when compared with traditional cultivars. Consumers were willing to pay a premium for colored-flesh potatoes if they were educated on their potential health benefits. Phenolic content and antioxidant activity of purple-fleshed potatoes, after baking, were comparable with those of anthocyanin-rich berries. Hence, locally grown purple-fleshed potatoes can be a healthier choice as they possess greater levels of bioactive compounds and in vitro anti-cancer properties even after processing as compared to their white- and yellow-fleshed counterparts.
Keywords: colon cancer; polyphenolic content; potato; processing; sensory analysis; storage